Fishing boats at anchor at Fisherman's Wharf - Albert Walton DeRome:::Creator::::::::::::
Lamparas, lighters and skiffs at anchor, probably at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. Photo is a bit out of focus. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)